Emotionally-Focused Therapy and Marital Bonding: Counselling Implications for Nigerian Couples - Sunmonu, Hikmot Oluwatoyin; Tiamiyu, Kamoru Abidoye; Yusuf, Jamila; Ahmed, Mustapha Shina (Universitas Islam Bunga Bangsa Cirebon, 2025)
Marital bonding is a crucial foundation for stable and satisfying marriages, yet many Nigerian couples face challenges such as emotional distance, communication breakdowns, financial strain, and extended family interference. These pressures often erode intimacy and increase vulnerability to marital dissatisfaction, infidelity, or divorce. Against this backdrop, Emotionally-Focused Therapy (EFT) has emerged globally as one of the most empirically validated interventions for strengthening emotional intimacy and repairing attachment injuries. However, its application within non-Western, collectivist societies such as Nigeria remains underexplored. The purpose of this study is to examine the relevance of EFT as a counselling strategy for enhancing marital bonding among Nigerian couples, with a particular focus on married teachers in Kwara State who navigate dual career responsibilities alongside family obligations. This paper employed a conceptual and analytical method, synthesising international and Nigerian literature on EFT, marital bonding, and the socio-cultural dynamics of marriage. The analysis highlighted how EFT principles can be adapted to Nigerian realities shaped by extended kinship systems, evolving gender roles, and religious expectations. The main findings indicate that EFT fosters emotional intimacy, trust, and empathy, making it a culturally adaptable tool for addressing marital disconnection. Nigerian studies affirm that EFT improves emotional regulation, reduces conflict linked to external family pressures, and strengthens communication between partners. The study concludes that EFT not only has universal applicability but also offers unique value when localised to Nigerian cultural contexts. Its contribution lies in demonstrating that counselling models developed in Western settings can be meaningfully adapted to collectivist societies, thereby promoting marital resilience, family stability, and community well-being.